2017
DOI: 10.1016/j.mri.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing data from GABA-edited MEGA-PRESS implementations at 3 Tesla

Abstract: Standardization of results is an important milestone in the maturation of any truly quantitative methodology. For instance, a lack of measurement agreement across imaging platforms limits multisite studies, between-study comparisons based on the literature, and inferences based on and the generalizability of results. In GABA-edited MEGA-PRESS, two key sources of differences between implementations are: differences in editing efficiency of GABA and the degree of co-editing of macromolecules (MM). In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Unsuppressed water was used for water scaling and correction of frequency and phase. The spectra were fitted using TARQUIN software (Wilson et al, 2011; Mullins et al, 2014; Harris et al, 2017). GABA peaks were quantified calculated using the water-scaled method, as described previously (Wilson et al, 2011; Mullins et al, 2014; Harris et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Unsuppressed water was used for water scaling and correction of frequency and phase. The spectra were fitted using TARQUIN software (Wilson et al, 2011; Mullins et al, 2014; Harris et al, 2017). GABA peaks were quantified calculated using the water-scaled method, as described previously (Wilson et al, 2011; Mullins et al, 2014; Harris et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…92 The relative contributions of GABA and MM to the edited GABA+ resonance also depend on the timing pattern of the editing pulse. 107 Improving the selectivity of the editing pulse by performing single quantum editing with a numerically optimized pulse has been used to reduce MM coediting. 108 Additional strategies could be employed using multiple quantum filtering to reduce MM coediting by adjusting the frequency separation between the two frequency selection bands and by repeating the double-band selective pulse.…”
Section: Mm-coediting In Spectral Editing (Gaba+)mentioning
confidence: 99%
“…Conversely, a higher bandwidth will reduce the susceptibility to misadjustment of the editing pulse frequency caused by motion and field drift, 106 which alters MM coediting 92 . The relative contributions of GABA and MM to the edited GABA+ resonance also depend on the timing pattern of the editing pulse 107 …”
Section: Mm‐coediting In Spectral Editing (Gaba+)mentioning
confidence: 99%
“…A large multi-site study involving diverse implementations of MEGA-PRESS across sites and vendors revealed relatively good agreement (albeit with statistically significant differences) between sites and vendors. This study suggested that approximately 30% of the total variance in the GABA þ data was attributed to site-and vendor-level differences in the implementation of MEGA-PRESS (Mikkelsen. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%